EFFECT OF WORKING CAPITAL MANAGEMENT ON PROFITABILITY OF LISTED CONSUMER GOOD COMPANIES IN NIGERIA - Ijuwo, Amity (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
This ex post facto study investigates the effect of Working Capital Management (WCM) on the profitability of 10 listed consumer goods companies in Nigeria over the period 2017-2022. Utilizing a panel data analysis framework with fixed and random effect regression, Jarque Bera statistics and Breusch-Pagan LM for assessing heteroscedasticity, the study reveals valuable insights into the relationship between WCM variables and Return on Assets (ROA). The positive and significant coefficient of 0.000617 for the Cash Conversion Cycle (CCC) suggests that a deliberate and strategic extension of the cash conversion cycle is associated with increased profitability. The study also explores the intricate relationships, revealing that fluctuations in inventory turnover, variations in accounts receivables and payables, and certain firm characteristics like size and leverage may not be robust determinants of profitability. These findings emphasize the need for tailored working capital management strategies based on specific industry characteristics and organizational contexts. The study's implications underscore the importance of meticulous cash conversion cycle management for consumer goods companies seeking to optimize financial health and operational effectiveness. While inventory turnover, accounts receivables, and accounts payables are crucial components of WCM, their individual variations may not be decisive factors influencing overall financial success. This research contributes to the growing body of evidence on the intricate relationship between WCM and profitability, offering valuable insights for financial decision-makers in the consumer goods sector in Nigeria.